Evaluation of Monoclonal and Oligoclonal Gammopathies in a Pediatric Population in a Major Urban Center. Issue 4 (1st April 2014) - Karafin, Matthew S.; Humphrey, Richard L.; Detrick, Barbara
Abstract: Objectives: A growing body of literature has documented monoclonal proteins in children. Little is known about their associated diagnoses. Methods: We retrospectively evaluated all patients (aged 0–21 years) with abnormal findings on serum immunofixation electrophoresis (SIFE) from 2005 to 2011. We also documented the monoclonal immunoglobulin classes and light chain types involved and then correlated these data with the clinical diagnoses. Results: A total of 695 SIFE tests were performed on this patient population. Of these, 95 SIFE tests (14%) identified a gammopathy (from 83 different patients), and of these, 74 (11%) demonstrated only a monoclonal gammopathy (from 63 different patients). The most common associated diagnosis in the study interval was ataxia-telangiectasia (22%). No patient in the study population was diagnosed with multiple myeloma or Waldenström macroglobulinemia. Conclusions: The significance and presence of a monoclonal or oligoclonal gammopathy in pediatric and young adult populations is distinct from that seen in adults.